2021
DOI: 10.1111/tbed.14273
|View full text |Cite
|
Sign up to set email alerts
|

Belgian bulk tank milk surveillance program reveals the impact of a continuous vaccination protocol for small ruminants against Coxiella burnetii

Abstract: Endemic Q fever in small ruminants remains an ongoing challenge for veterinary and human public health agencies. Though surveillance programs are implemented in Belgium, infection patterns and vaccination profiles, driving variables, as well as geographical clustering were not presented until now. Based on data from a decade of bulk tank milk analysis between 2009 and 2019, shedding in dairy goat herds declined from 16% (8/50) to 6% (10/162), whereas seroprevalence remained between 32% and 40%. Merely up to tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 62 publications
1
16
0
Order By: Relevance
“…Bulk tank milk (BTM) samples have been successfully used to monitor the Q fever status of dairy goat herds [ 33 , 34 , 35 ]. Analyzing caprine BTM samples for C. burnetii by PCR revealed a wide range of detection rates in several countries, such as 16% in Belgium [ 35 ], 32.9% in the Netherlands [ 34 ], 54% in Poland [ 36 ], and 16.1% in Iran [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bulk tank milk (BTM) samples have been successfully used to monitor the Q fever status of dairy goat herds [ 33 , 34 , 35 ]. Analyzing caprine BTM samples for C. burnetii by PCR revealed a wide range of detection rates in several countries, such as 16% in Belgium [ 35 ], 32.9% in the Netherlands [ 34 ], 54% in Poland [ 36 ], and 16.1% in Iran [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bulk tank milk (BTM) samples have been successfully used to monitor the Q fever status of dairy goat herds [ 33 , 34 , 35 ]. Analyzing caprine BTM samples for C. burnetii by PCR revealed a wide range of detection rates in several countries, such as 16% in Belgium [ 35 ], 32.9% in the Netherlands [ 34 ], 54% in Poland [ 36 ], and 16.1% in Iran [ 37 ]. However, this method is limited to dairy animals, and there is a growing interest to examine dust samples from animal facilities to detect C. burnetii on ruminant farms [ 3 , 6 , 38 , 39 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…Q fever in mammals is generally asymptomatic; however, pregnant livestock will manifest reproductive disorders, such as abortion, stillbirth, and mastitis. Large amounts of pathogens are not only shed during abortion or normal parturition, but also through milk, vaginal mucus, and feces for months [ 57 ]. The routes of human infection include direct contact with shedders, eating raw meat and milk of infected ruminants, or inhalation of contaminated aerosols [ 58 ].…”
Section: Tick-borne Bacteriamentioning
confidence: 99%
“…Effective action of Coxevac® is usually achieved following compliant multiannual vaccination protocols, but filed data indicated that protective antibody levels are not maintained long enough to establish standardized yearly vaccination programs 19 . Given that Coxevac® does not contain an adjuvant and the need to increase its efficacy, we designed an improved formulation of Coxevac® by including the readyto-use QuilA® adjuvant in the emulsion.…”
Section: Vaccination-challenge Experiments In Goatsmentioning
confidence: 99%
“…Although several studies demonstrated its efficacy in reducing clinical signs (abortions) and bacterial shedding [13][14][15][16] , this vaccine does not prevent infection 13,15 nor clears the infection in infected animals 17,18 . In addition, field data indicated that antibody levels decrease after 9 months below protective levels, hampering targeted annual vaccination programs on herd level 19 . If the critical level of protective immunity is not maintained long enough at the individual or herd level, recrudescence will likely take place 19,20 .…”
Section: Introductionmentioning
confidence: 99%